A cytogenetic study of men occupationally exposed to uranium. Issue 2 (February 1991) - Martin, F; Earl, R; Tawn, E J
Abstract : Blood lymphocyte cultures from two groups of workers occupationally exposed to uranium were examined for asymmetrical chromosome aberrations and sister chromatid exchanges (SCEs). Significant increases in both cytogenetic endpoints were seen. For dicentrics this appeared to be particularly associated with exposure to soluble uranium. The external radiation exposure experienced by these men was insufficient to explain the increase in dicentrics, and irradiation of lymphocytes by internally deposited uranium would have been minimal. As the SCEs were also raised, the genotoxic effect is likely to be due to the chemical nature of the compound. The increase in frequency of dicentrics associated with smoking was greatest in the group with exposure to soluble uranium suggesting some interaction between the two clastogens. No such interactive effect was seen for SCE frequencies, in which increases attributable to smoking were similar in the worker and control groups.